Preparation of ternary composite (WS2-FeOCl-PANI) and its performance as auxiliary electrode in electrokinetic remediation of simulated Cr(VI) contaminated soil. Issue 6 (December 2021) - Zhao, Dingsheng; Liu, Xiao; Peng, Mingguo; Cheng, Yuhan; Zhang, Wenyi; Hu, Linchao; Mao, Linqiang
Abstract: The utilization of an auxiliary electrode is a promising approach for improving the electrokinetic remediation efficiency of anionic metal contaminated soil. In this study, the ternary composite of Tungsten disulfide-Iron oxychloride-Polyaniline (WS2 -FeOCl-PANI) was synthesized and employed as an auxiliary electrode for electrokinetic remediation of simulated Cr(VI) contaminated soil. The ternary composite of WS2 -FeOCl-PANI was successful prepared by the polymerization of aniline monomer on the surface of WS2 -FeOCl, and its specific capacitance was enhanced to 268 F/g, which was higher than PANI by 87.9%. The application of WS2 -FeOCl-PANI as an auxiliary electrode improved remarkably the electrical migration and the electric field distribution. The current was elevated from 128 mA to 225 mA, and electric potential difference was extended from 17.9 V to 23.6 V. The removal ratio of total Cr with the use of WS2 -FeOCl-PANI was enhanced significantly, which is higher by 20% than that without an auxiliary electrode. Meanwhile, the reduction ratio of Cr(VI) in contaminated soil was promoted to around 90%. The combined actions of PANI and S 2- are mainly responsible for the considerable reduction of Cr(VI). This study provides an excellent auxiliary electrodes material for improving electrokinetic remediation of Cr(VI) contaminated soil. Graphical Abstract: ga1 Highlights: The high specific capacitance of WS2 -FeOCl-PANI was prepared. The use of WS2 -FeOCl-PANI enhanced removal efficiency of total Cr by 20%. More than 90% of Cr(VI) was reduced with the help of WS2 -FeOCl-PANI. The reduction of Cr(VI) is strongly dependent on PANI and S 2- .